Strategi Abduktif-Deduktif Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Eline Yanty Putri Nasution; Ayu Dasmina; Selvia Erita (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2022)
The background in this research is the lowerness of students’ problem solving skill. This research aim to improve students' problem solving skill by using abductive-deductive strategies. This research used the quasi-experimental method with the Control Group Pretest-Posttest design. The research population was all of VIII grade students in SMPN 4 Kerinci. We use the survey technique to determine the research sampel. The sample of this research was students of VIII A grade as the control class and the students of VIII B grade as the experimental class. The research instruments used in this research is problem solving ability test. The pretest was given before the learning begun then the posttest was given after the learning process. The results of this research indicate that students in the experiment class have better problem solving skills than the control class. The conclusion of this research was the abductive-deductive strategies can improve the students’ problem solving ability.